2012
DOI: 10.1159/000335724
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Occlusion or Not during Liver Resection: The Continuing Story

Abstract: <i>Background:</i> Vascular occlusion can be applied during liver resection to reduce blood loss. Herein, we provide an update of the current evidence concerning vascular occlusion. <i>Methods:</i> A systematic literature search was conducted to review the effects of liver in- and outflow occlusion techniques during liver resection, focusing on blood loss and hepatic ischemia-reperfusion injury. <i>Results:</i> The Pringle maneuver (PM) is effective in controlling blood loss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 117 publications
1
31
0
2
Order By: Relevance
“…A Cochrane review of vascular occlusion methods for elective liver resections concluded that intermittent portal clamping is safe and decreases blood loss but not morbidity [26], and it found that ischaemic pre-conditioning further decreases blood loss and transfusion requirements as well as decreases intensive care unit and overall hospital stay [27]. A further review also agrees with this, but also suggested the use of total vascular exclusion techniques when tumours involve the IVC or the caval confluence with the hepatic veins [28]. …”
Section: Discussionmentioning
confidence: 89%
“…A Cochrane review of vascular occlusion methods for elective liver resections concluded that intermittent portal clamping is safe and decreases blood loss but not morbidity [26], and it found that ischaemic pre-conditioning further decreases blood loss and transfusion requirements as well as decreases intensive care unit and overall hospital stay [27]. A further review also agrees with this, but also suggested the use of total vascular exclusion techniques when tumours involve the IVC or the caval confluence with the hepatic veins [28]. …”
Section: Discussionmentioning
confidence: 89%
“…These include the continuous or intermittent Pringle Maneuver (PM), the total hepatic vascular exclusion (THVE), and the hemihepatic or segmental occlusion of the portal vein or hepatic artery (40). Sadly, the aforementioned methods are accompanied by negative effects such as the hepatic IRI (6).…”
Section: Surgical Methods Used To Reduce Hepatic Irimentioning
confidence: 99%
“…The optimal ischemic intervals are still debated and numerous studies try to define the optimal PM cycle. All in all, ischemic intervals of 30 minutes can be safely used followed by 5 minutes of reperfusion (40). According to der Broek et al there were no significant differences between ischemic intervals of 15 minutes and 30 minutes as far as hepatocellular injury, median blood loss, liver function and morbidity are concerned (42).…”
Section: Surgical Methods Used To Reduce Hepatic Irimentioning
confidence: 99%
“…However, studies have showed that Pringle maneuver can induce intestinal epithelial cell damage and deteriorate gut barrier dysfunction, which is associated with indirect severe clinical complications, namely multiple remote organ injuries [27].The insult from liver I/R injury [11] or mesenteric congestion secondary to prolonged occlusion of the portal vein [23] could be the main reasons. Moreover, occlusion of hepatic blood flow during hepatectomy is not obligatory because many liver resections have been performed successfully in its absence [15,25]. Take together, it may be advisable to avoid the routinely use of Pringle maneuver to reduce the GI complications.…”
Section: Discussionmentioning
confidence: 99%